Polar riometer observations - Cormier, Raymond J.; Air Force Cambridge Research Laboratories (U.S.)
Qualitative descriptions of the morphology of Polar Cap Absorption (PCA) events are given, using data from the following riometer stations: Thule and Godhavn, Greenland; Churchill Range, Manitoba, Canada; and Reykjavik (Leirvogur), Iceland. The dependence of commencement time on solar zenith angle and subsequent daily variations in absorption following the initial day are described. The morphology of PCA events is very important for forecasting the behavior of ionospheric absorption during a PCA event. It is shown that besides information concerning the energy spectrum of the proton flux, the season and time of day must also be considered for forecasting the expected absorption. (Author). Research supported by the Air Force Cambridge Research Laboratories, Air Force Systems Command, United States Air Force, L.G. Hanscom Field, Bedford, Massachusetts. Ionospheric Physics Laboratory Project 5631. AD0721183 (from http://www.dtic.mil). "3 December 1970." Includes bibliographical references (page 15). Qualitative descriptions of the morphology of Polar Cap Absorption (PCA) events are given, using data from the following riometer stations: Thule and Godhavn, Greenland; Churchill Range, Manitoba, Canada; and Reykjavik (Leirvogur), Iceland. The dependence of commencement time on solar zenith angle and subsequent daily variations in absorption following the initial day are described. The morphology of PCA events is very important for forecasting the behavior of ionospheric absorption during a PCA event. It is shown that besides information concerning the energy spectrum of the proton flux, the season and time of day must also be considered for forecasting the expected absorption. (Author). Mode of access: Internet.